Formation of Students' Soft Skills Through the Three-Language Speech Activity at MTs Al-Jihad Kerasaan - Nurfadillah, Annisa; Darlis, Ahmad (Journal of English Language and Education, 2025)
This qualitative study investigates the efficacy of a trilingual speech activity at MTs Al-Jihad Kerasan in developing students' soft skills, framing the activity as an integrated pedagogical model. Employing a descriptive qualitative approach, data were gathered through direct observation, interviews with teachers and students, and documentation. The data were then analyzed using the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing/verification. The analysis reveals that the trilingual speech activity serves as a multifaceted platform for holistic soft skill development. The structured process—comprising preparation, practice, evaluation, and intensive mentoring, and reinforced by a reward system—proves effective in cultivating a suite of competencies. These include communication skills, selfconfidence, presentation skills, creativity, critical thinking, adaptability, and emotional intelligence. Furthermore, the study identifies a unique symbiotic outcome: the simultaneous enhancement of linguistic proficiency in three languages and the strengthening of religious identity, multicultural awareness, and global perspectives. The trilingual speech model is a potent pedagogical strategy for soft skill integration in madrasah education. For future implementation, this study recommends the development of more innovative training methods and the provision of dedicated facilities, such as a speech practice room, to optimize outcomes. Subsequent research could quantitatively compare speech proficiency across the three languages to generalize the findings more broadly.